Edge Crack in Longitudinal Butt-Welded Joint in Thick-Wall Cylinder - Yunan Prawoto; Rachmad Imbang Trittjahjono (Jurnal Internasional Penelitian Teknologi Terapan, 2021)
Thick-wall vessels and pipes cylindrical shape are very typical in power plant, chemical, processing, oil and gas industry. The equipment with cylindrical shape can be either thin or thick wall which depends on the function of that particular equipment. Typically, thick-wall cylinder is used when the equipment is needed to accommodate high pressure contents. Mostly, cracks appear either on the internal or external of a thick-wall cylinder. Primarily, when welding is applied in the fabrication of the thick-wall cylinder, cracks can easily appear due to solidification or hydrogen embrittlement at the welded joint, typically butt-welded joint. Hence, it is critical to examine the stress distribution along the crack and resolve the stress intensity factor of the cracks in both welded and non-welded internally pressurized thick-wall cylinder. Finite element analysis has been conducted using the engineering software, ABAQUS CAE to investigate the stress distribution and to perform the evaluation of stress intensity factor. Besides, weight function method has also been used by other researchers to determine the factor of stress intensity for both welded and non-welded thick-wall cylinder. The results were compared in terms of both of the methods applied. The last, the effect of the butt-welded joint profile in thick-wall cylinder has also been investigated.